Kontak Bahasa antara Komunitas Tutur Dialek Bira dengan Komunitas Tutur Bahasa Sumbawa di Kecamatan Buer Kabupaten Sumbawa - putra, erwinsyah; najamudin, najamudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The purpose of this study is to answer the form of linguistic adaptation between the Bira dialect speech community and the Sumbawa language speech community in Buer District, Sumbawa Regency. The method used is descriptive qualitative. The data collection stage begins with observation, interview techniques, and recording techniques. Furthermore, the listening method is widely used by tapping techniques as the basic technique, as well as listening to conversational techniques, recording techniques, and note-taking techniques as a follow-up technique. The collected data were analyzed using the intralingual equivalent method. The data were validated by triangulation technique and using an interactive analysis model.The results of the study revealed that the form of linguistic adaptation in the Bira dialect speech community to the Sumbawa language speech community in Buer District, Sumbawa Regency was only at the level of phonological absorption and lexicon absorption. The form of linguistic adaptation that occurs is only seen in speakers of the Bira dialect, while Sumbawa speakers do not make linguistic adaptations. The process of linguistic adaptation in the form of phonological absorption and lexicon absorption is carried out by young speakers and old speakers of the Bira dialect. The form of phonological absorption from the Samawa language to the Bira dialect was found as many as eight data. The eight phonological absorption data were absorbed by young speakers, while the forms of phonological absorption in older speakers were not found. The data in the form of linguistic adaptations shown by speakers of the Bira dialect at the lexicon level were found to be fifteen lexicon absorptions. Young speakers of the Bira dialect absorb the Sumbawa language lexicon as many as thirteen absorptions and the old speakers of the Bira dialect only absorb two of the Sumbawa language lexicon. Thus, young speakers of the Bira dialect in Buer District, Sumbawa Regency are said to be more dominant in making linguistic adaptations at the level of phonological absorption and lexicon absorption compared to older speakers of the Bira dialect.